2001
DOI: 10.1046/j.1420-9101.2001.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetic differentiation at marker loci and quantitative traits

Abstract: The comparison of the degree of differentiation in neutral marker loci and genes coding quantitative traits with standardized and equivalent measures of genetic differentiation (FST and QST, respectively) can provide insights into two important but seldom explored questions in evolutionary genetics: (i) what is the relative importance of random genetic drift and directional natural selection as causes of population differentiation in quantitative traits, and (ii) does the degree of divergence in neutral marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
933
7
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,125 publications
(1,014 citation statements)
references
References 103 publications
40
933
7
2
Order By: Relevance
“…Underprediction on short timescales suggests that diversifying selection has produced departures from neutrality. This result is common in studies of divergence among local populations, for example, when assessed by F ST -Q ST comparisons (Merilä and Crnokrak 2001;McKay and Latta 2002). On such short timescales, adaptation to spatially varying selection is often rapid, so that phenotypic divergence exceeds neutral rates.…”
Section: Interpretation Of Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Underprediction on short timescales suggests that diversifying selection has produced departures from neutrality. This result is common in studies of divergence among local populations, for example, when assessed by F ST -Q ST comparisons (Merilä and Crnokrak 2001;McKay and Latta 2002). On such short timescales, adaptation to spatially varying selection is often rapid, so that phenotypic divergence exceeds neutral rates.…”
Section: Interpretation Of Resultsmentioning
confidence: 93%
“…These approaches assess the statistical significance of departures from neutral rates of evolution. Enough empirical tests have been performed to provide general conclusions: on short timescales, rates are typically faster than expected under neutrality (Merilä and Crnokrak 2001;McKay and Latta 2002), but on long timescales, they are usually slower-often much slower (Lynch 1990;Hansen and Houle 2004;Estes and Arnold 2007). We can with confidence reject the general hypothesis that rates of trait evolution at all timescales conform to neutral expectations.…”
mentioning
confidence: 87%
“…The magnitude of selection in natural populations can be approached by complementing spatial studies of neutral variability with distribution patterns of traits. A popular approach has been to compare population structure at neutral markers versus selected traits, the so-called F ST versus Q ST approach (review in Merilä and Crnokrak, 2001; see Chapuis et al, 2007 for a recent reference). This approach may help unraveling the nature of selection.…”
Section: Introductionmentioning
confidence: 99%
“…resistance to chloroquine in Plasmodium falciparum [189] and to benzimadazole in Haemonchus contortus [190]), most of the parasite traits which interest us from an epidemiological viewpoint are likely to be polygenic, quantitative traits [19]. A number of studies over a wide range of taxa have shown that there is a poor correlation between the among-group genetic variance in neutral, single gene markers (typically measured by F ST ) and the among-group genetic variance in complex, quantitative traits (as measured by Q ST ) [191][192][193].…”
Section: Markers For Traits Of Epidemiological Importancementioning
confidence: 99%